Perspectives on Sub–Nanometer Level of Electronic Structure of the Synchrotron with Mendelevium Nanoparticles for Elimination of Human Cancer Cells, Tissues and Tumors Treatment Using Mathematica 12.0 - Heidari, Alireza; Schmitt, Katrina; Henderson, Maria; Besana, Elizabeth (Journal of Energy Conservation, 2019)
Mendelevium nanoparticles absorb energy of descendent light and generate some heat in the particle. The generated heat transferred to the surrounding environment and leads to increase in temperature of adjacent points to nanoparticles. Heat variations can be obtained by heat transfer equation. In the current study, thermoplasmonic characteristics of Mendelevium nanoparticles with spherical, core–shell and rod shapes are investigated. In order to investigate these characteristics, interaction of synchrotron radiation emission as a function of the beam energy and Mendelevium nanoparticles were simulated using 3D finite element method. Firstly, absorption and extinction cross sections were calculated. Then, increases in temperature due to synchrotron radiation emission as a function of the beam energy absorption were calculated in Mendelevium nanoparticles by solving heat equation. The obtained results show that Mendelevium nanorods are more appropriate option for using in optothermal human cancer cells, tissues and tumors treatment method. When Mendelevium nanoparticles are subjected to descendent light, a part of light scattered (emission process) and the other part absorbed (non–emission process). The amount of energy dissipation in non–emission process mainly depends on material and volume of nanoparticles and it can be identified by absorption cross section. At the other hand, emission process which its characteristics are depend on volume, shape and surface characteristics of nanoparticles explains by scattering cross section. Sum of absorption and scattering processes which lead to light dissipation is called extinction cross section.
Keywords: Mendelevium Nanoparticles; Synchrotron Radiation; Thermoplasmonic; Heat Transfer Equation; Human Cancer Cells